Nutrigenomics: Epigenetics and cancer prevention: A comprehensive review - Nasir, Ayesha; Bullo, Mir. M. Hassan; Ahmed, Zaheer; Imtiaz, Aysha; Yaqoob, Eesha; Safdar, Mahpara; Ahmed, Hajra; Afreen, Asma; Yaqoob, Sanabil (Critical reviews in food science and nutrition, 2020)
Due to change in lifestyle and food habits, people are more at risk of diet-related diseases and cancers. It is also established that dietary modifications significantly reduce the risk of diseases. Nutrigenomics is relatively fresh discipline, but possess an enormous potential that can apply for prevention and management of certain carcinomas and diseases. This review enables us to generate useful information for scientists and health professionals regarding the role of Nutrigenomics in the prevention of diet and lifestyle-related diseases like cancer. It influences health conditions of individuals and susceptibility of disease by defining the metabolic response and gene expression. Epigenetic modifications can perform a significant role in disease occurrence and pathogenesis. DNA methylation and chromatin remodeling are the most common epigenetic mechanisms. Omega 3 fatty acids are the best example of nutrients and gene interaction not involving DNA methylation while certain bioactive food compounds have a proven role in cancer prevention through an epigenetic mechanism. Dietary polyphenols substantially take part in prevention of oral, breast, skin, esophageal, colorectal, prostate, pancreatic and lung cancers. Moreover, minerals and vitamins involve regulatory processes. Zinc, Selenium and folate involve in DNA repairing process have anticancer properties. Consumption of multivitamins prevents methylation of cancer cells.